Membangun loyalitas melalui kualitas sistem, kualitas informasi, dan kualitas layanan dengan kepuasan pelanggan sebagai mediasi - Cahyadi, Bardani Bias; Shihab, Muchsin Saggaf (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This thesis is the result of quantitative research which aims to analyze the factors that influence customer satisfaction of GreatDay HR users to increase Customer Loyalty. Research data was collected through the distribution of questionnaires as primary data and secondary data based on the results of previous research literature studies. Furthermore, it is analyzed by quantitative descriptive analysis, through correlational studies to analyze the causality relationship between research variables in accordance with the compiled hypothesis. In the t-test the results state that there is a positive and significant impact between system quality, information quality, and service quality on customer satisfaction. Furthermore, the results of the study stated that there was a positive and significant impact between system quality and customer satisfaction on customer loyalty. The result of the ttest of the variable that has the most impact on customer satisfaction is the quality of the system with a large effect of 37%. In the Path Analysis Test, the results stated that the quality of information and service quality had a direct negative and insignificant effect on customer loyalty, while the quality of the system had a direct positive and significant effect on customer loyalty. In line with the conclusions above, it is recommended that GreatDay HR companies and other similar application service providers should improve customer satisfaction in order to create customer loyalty by developing system quality, information quality, and service quality.